Thyroid Carcinoma Patients Correlated With Cytomegalovirus by using Insitu Hybridization - Noor Al-Huda Ali A.H. Saeed 1 , Ban Talib Elhaboby 2 , Wasan A. Wahab Alsiadi3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Worldwide, the most common cancer-related deaths and poses one of the top ten most risk cancers globallyin many countries, is the thyroid carcinoma. In human cancers, there are important factor associated withit . The viral agent is one of them which is involved in the spread of tumors, including thyroid cancers. So,the present study was designed to determine the relationship between Cytomegalovirus infection with someIraqi patients who suffer from the thyroid carcinoma in tissue cancer from different site (papillary, follicularand lymph node) by using In Situ Hybridization Technique, related to their age, gender, site distribution,histological grade and the tumor stage. The sixty biopsies were randomly collected during the period betweenJune 2017 until October 2018,CMV was detected in(28.3%)(17 out of 60 patients, the mean age was 39years old, ranged between ( 27-72) years old, female to male ratio was (1.3 : 1) with 34 women and 26 men.The most of these cases were papillary carcinoma 39, followed by follicular 13 and the rest 8 cases were atthe lymph node. Histological grades that involved were 37 well differentiated, 18 were poorly differentiated,and 5 were moderately differentiated. Tumor staging included 43 patients who fall in stage I and II, whilethe rest 17 patients fall in stage III and IV. Regarding to the positive results, CMV correlates in a highlysignificant association with each of (age, gender, grading, tumor stage, and site distribution at p<0.01).It could be concluded from that the in situ hybridization is useful in the clinical evaluation of patients withthyroid carcinoma. And suggested that the viral agent cytomegalovirus is involved in thyroid carcinogenesisand may play an important role in the malignant transformation of thyroid cancer.